Contrast‐enhanced ultrasound‐guided Sentinel lymph node biopsy of the ocular conjunctiva. (13th June 2014) - Rabinowitz, Mindy R.; Merton, Daniel A.; Liu, Ji‐Bin; Saxena, Shivam; Pluta, John; Eisenbrey, John R.; Baker, Adam L.; Rabinowitz, Michael P.; Lally, Sara; Cognetti, David; Goldberg, Barry B.; Pribitkin, Edmund A.; et al.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Sentinel lymph node biopsy (SLNB) has been utilized for cutaneous melanoma and other malignancies arising from the eye and ocular adnexa. Currently, SLNB requires blue dyes and/or radiopharmaceuticals; both of which have significant shortcomings. This study sought to evaluate the feasibility of SLNB with the use of real‐time, contrast‐enhanced ultrasound (CEUS) as an alternative technique for tumors arising in the conjunctiva. Study Design Prospective feasibility study in a porcine model. Methods Twelve experiments were performed on six non–tumor‐bearing Yorkshire swine. An ultrasound contrast agent, Sonazoid (GE Healthcare, Oslo, Norway), 99mtechnetium (99mTc), and methylene blue (MB) (Covidien, Mansfield, MA) were injected in the ocular conjunctiva. Sentinel lymph nodes (SLNs) were localized with CEUS and findings were compared to that of MB and 99mTc. Fisher exact test was used. Results Contrast‐enhanced SLNs were identified within an average of 6.2 minutes from time of injection of Sonazoid. A total of 17 SLNs were identified by at least one of the three techniques. Correlation between Sonazoid and 99mTc was 94.1% (16/17 SLNs). Correlation between 99mTc and MB was 88.2% (15/17). One SLN that was positive for 99mTc but negative for Sonazoid and was considered to be a false positive (1/17); findings were similar for MB (1/17). Differences between the three techniques were not significant (P = .886). Conclusions CEUS‐guided injection of conjunctiva for SLNB is technically feasible and correlates well with standard detection techniques. This technique shows promise for rapid, real‐time, intraoperative imaging for SLNB, using a widely available imaging modality and avoiding the need for radiopharmaceuticals. Level of Evidence NA Laryngoscope, 124:2531–2536, 2014